Analysis Of The Level Of Basic Pencak Silat Skills Of Athletes Of The Satria Ash-Syuhada College In Deli Serdang District - Ayub, Farahdiba Ardhana; Lubis, Ade Evriansyah (Educational Sciences Journal, 2025)
This study aims to determine the level of basic skills of pencak silat athletes at the As-Syuhada Satria College of Deli Serdang. This research is a descriptive study characterized by the absence of a hypothesis and the data obtained will be presented. The method used is a survey method with test and measurement techniques that aim to find out empirical data on the basic skill level of pencak silat at the Satria Asy-Syuhada Deli Serdang College. Based on the results of the research and discussion that 1 athlete falls into the less category (6.25%) and 15 athletes fall into the very poor category (93.75%), it can be concluded that the basic skill level of pencak silat athletes participating in the Satria Pencak Silat college Asy-Syuhada Deli Serdang is included in the very less category.